THE CONTINUING EDUCATION OF POLICE OFFICERS: REFLECTIONS ON POLICE APPROACH AND THE "STANDARD COLOR ELEMENT" - Castiajo, Daniel (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes the production of legal inequality in the Brazilian justice system through a dialogue between Law and Social Sciences. It begins with a historical understanding of citizenship in Brazil to highlight how the formal recognition of rights coexists with selective institutional practices. The research adopts a theoretical-analytical approach, based on authors from legal sociology and the anthropology of law, with emphasis on studies on legal equality, institutional moralities, and police ethics. It argues that equality before the law, although constitutionally guaranteed, is operationalized differently in the daily life of institutions, incorporating pre-existing social inequalities. The article demonstrates that legal decisions and police practices are guided by moral classifications, implicit values, and extra-legal criteria that influence the recognition of rights and the management of conflicts. The analysis shows that legal inequality does not result from isolated failures, but constitutes a structural element of the functioning of the justice system, manifesting itself from the initial stages of contact between the citizen and the State to judicial action. It is concluded that overcoming this situation requires not only normative reforms, but also a critical problematization of the institutional practices and moralities that underpin legal selectivity in the Brazilian context.